2017
DOI: 10.1007/s00520-017-3720-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of prophylactic growth factors and antimicrobials in elderly patients with cancer: a review of the Medicare database

Abstract: Purpose Growth factors and antimicrobials can reduce complications of chemotherapy-induced myelosuppression. Their prophylactic use in elderly patients is important given the associated comorbidity in this age group. There is a developing trend by payers to include supportive care agents in chemotherapy care bundles, which could affect clinical practice. We examined whether the febrile neutropenia (FN) risk categories can be used to describe utilization in the Centers for Medicare & Medicaid fee-for-service sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
(23 reference statements)
4
6
0
3
Order By: Relevance
“…Our results are consistent with prior studies that reported suboptimal use of prophylactic G-CSF [24,25]. Ramsey [25].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are consistent with prior studies that reported suboptimal use of prophylactic G-CSF [24,25]. Ramsey [25].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with prior studies that reported suboptimal use of prophylactic G-CSF [ 24 , 25 ]. Ramsey and colleagues linked the Western Washington State Surveillance, Epidemiology, and End Results (SEER) registry data with data from 4 major insurers (Medicare, Medicaid, Premera Blue Cross, and Regence Blue Shield) for patients treated for breast cancer, non-small cell lung cancer, and colorectal cancer from 2002 to 2005 [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the USA, the real-world use of G-CSF among patients at high risk of FN does not reflect the recommendations of national guidelines. G-CSF prophylaxis is observed in 17 to 74% of patients receiving chemotherapy regimens associated with high risk of FN, suggesting underutilization of an important preventive measure [14][15][16]. There is a paucity of information regarding the decision-making process employed by oncologists in determining the use of G-CSF prophylaxis for appropriate patients.…”
Section: Introductionmentioning
confidence: 99%